#### Answer

$P(a) = 2a-3$
$P(-x) = -(2x+3)$
$P(x+h) = 2x+2h-3$

#### Work Step by Step

If $P(x) = 2x-3$
$P(a) = 2a-3$
$P(-x) = 2(-x) -3 = -2x-3 = -(2x+3)$
$P(x+h) = 2(x+h)-3 = 2x+2h-3$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

$P(a) = 2a-3$
$P(-x) = -(2x+3)$
$P(x+h) = 2x+2h-3$

If $P(x) = 2x-3$
$P(a) = 2a-3$
$P(-x) = 2(-x) -3 = -2x-3 = -(2x+3)$
$P(x+h) = 2(x+h)-3 = 2x+2h-3$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.